Microencapsulação de óleos essenciais de orégano e canela combinados com ação sobre Listeria monocytogenes em produto cárneo - Gottardo, Franciele Maria (2021)
Meat products are classified as perishable foods and have favorable conditions for the multiplication of microorganisms such as Listeria monocytogenes, an important pathogen associated with ready-to-eat foods. Essential Oils (OEs) are promising natural antimicrobials for use in industry, but their characteristic flavor and aroma can impair consumer acceptance. Thus, in this study, the anti-Listeria potential of isolated and combined cinnamon and oregano OEs was evaluated, tested in an encapsulated meat matrix. The most efficient treatment applied to Italian type salami, checking consumer acceptability. Initially the isolated and combined OEs of cinnamon and oregano were evaluated in assays of Agar Diffusion and Minimum Inhibitory Concentration (MIC) with the following proportions established: 100% oregano (T1), 100% cinnamon (T2), 80% oregano / 20% cinnamon (T3), 50% oregano / 50% cinnamon (T4), 20% oregano / 80% cinnamon (T5). The most effective treatment was evaluated by gas chromatography (T4 - 50:50) and in isolation, evaluating the composition of each OE and the synergism in OEs combined. The combination of OE with the best anti-Listeria action was encapsulated by simple coacervation with sodium alginate, cross-linked with calcium chloride in an atomizer and lyophilized. The capsules were evaluated for encapsulation efficiency (EE), morphology and action against L. monocytogenes in a meat matrix with concentrations of 1.5%, 2%, 2.5% and 3%. Empty sodium alginate (TA) or OE (50% cinnamon / 50% oregano - TOE) capsules were added to Italian type salamis, a control sample without capsules (C) was also produced. Salamis were evaluated for technological and microbiological properties in addition to sensory evaluation. The main components found in cinnamon and oregano OE were cinnamaldehyde (85.55%) and carvacrol (91.1%), respectively. All treatments showed inhibition of L. monocytogenes in Agar Diffusion and inhibition with the application of up to 0.3 mg / mL in MIC. T4 (50% oregano / 50% cinnamon) showed the best anti-Listeria activity and was selected to be encapsulated, with an EE of 98.36%. When applied to meat matrix formulated as Italian type salami, the treatment with 2% capsule showed a significant reduction of L. monocytogenes in relation to the control. The acceptability index of TOE salami samples was 58.67%, while 84.99% for the control sample and 82.75% for the samples with only alginate capsules and the attributes found in CATA were bitter and spicy taste , acidic odor, dry texture, odor and essence flavor. The combined OE showed anti-Listeria potential and the microencapsulation technique allowed for high encapsulation efficiency. However, to improve the acceptability of the product added with OE, other techniques of application, encapsulation and release of OE may be necessary, as well as an extension of the food storage period with this treatment.